2019
DOI: 10.1164/rccm.201805-0879oc
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Leptin Relieves Sleep-disordered Breathing in Mice with Diet-induced Obesity

Abstract: Rationale: Leptin treats upper airway obstruction and alveolar hypoventilation in leptin-deficient ob/ob mice. However, obese humans and mice with diet-induced obesity (DIO) are resistant to leptin because of poor permeability of the blood-brain barrier. We propose that intranasal leptin will bypass leptin resistance and treat sleep-disordered breathing in obesity. Objectives: To assess if intranasal leptin can treat obesity hypoventilation and upper airway obstruction during sleep in mice with DIO. Methods: M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 42 publications
1
51
0
Order By: Relevance
“…Leptin-deficient ob/ob mice, hyperleptinemic and leptin resistant DIO mice, and New Zealand obese mice (NZO) hypoventilate during sleep, and retain CO 2 [ 157 , 171 , 172 , 173 ], similarly to patients with OHS. This defect was reversed by leptin delivery beyond the blood–brain barrier by intracerebroventricular [ 160 ] or intranasal routes [ 174 ]. In addition, both leptin deficiency and leptin resistance have a detrimental effect on upper airway collapsibility, leading to OSA [ 171 , 172 , 173 ], which has also been relieved by leptin delivery to the CNS [ 160 , 174 ].…”
Section: Metabolic Syndrome and Cb Chemosensory Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Leptin-deficient ob/ob mice, hyperleptinemic and leptin resistant DIO mice, and New Zealand obese mice (NZO) hypoventilate during sleep, and retain CO 2 [ 157 , 171 , 172 , 173 ], similarly to patients with OHS. This defect was reversed by leptin delivery beyond the blood–brain barrier by intracerebroventricular [ 160 ] or intranasal routes [ 174 ]. In addition, both leptin deficiency and leptin resistance have a detrimental effect on upper airway collapsibility, leading to OSA [ 171 , 172 , 173 ], which has also been relieved by leptin delivery to the CNS [ 160 , 174 ].…”
Section: Metabolic Syndrome and Cb Chemosensory Responsementioning
confidence: 99%
“…This defect was reversed by leptin delivery beyond the blood–brain barrier by intracerebroventricular [ 160 ] or intranasal routes [ 174 ]. In addition, both leptin deficiency and leptin resistance have a detrimental effect on upper airway collapsibility, leading to OSA [ 171 , 172 , 173 ], which has also been relieved by leptin delivery to the CNS [ 160 , 174 ].…”
Section: Metabolic Syndrome and Cb Chemosensory Responsementioning
confidence: 99%
“…Yao et al suggested the dorsomedial hypothalamus and nucleus tractus solitarius as the main site of the effects of leptin on ventilatory control, such as leptin relieving upper airway obstruction through the dorsomedial hypothalamus and its effect on respiratory pump muscles mediated by the nucleus tractus solitarius; however, the latter effect may be inhibited by increases in circulating leptin or even by leptin resistance [31]. Research on obese mice with leptin deficiency (ob/ob) shows that leptin can stabilize pharyngeal patency and ameliorate hypoventilation and upper airway obstruction in obesity [32,33], and that leptin replacement therapy can improve minute ventila- [34]. Besides, leptin acts on LepRb in the carotid body to stimulate breathing and the hypoxic ventilatory response, which may protect against sleep disordered breathing in obesity [35].…”
Section: Effect Of Leptin On the Upper Airwaymentioning
confidence: 99%
“…Lately, Berger et al found that intranasal leptin can reduce the number of oxygen desaturation events during rapid eye movement (REM) sleep and increase ventilation during non-REM and REM sleep in mice with diet-induced obesity. The authors thus suggested a new method of administration that bypasses leptin resistance and significantly attenuates sleep-disordered breathing independently of body weight [34]. This innovative approach demonstrates the potential of intranasal leptin for OSA treatment and provides us with new ideas, but it lacks strong evidence from clinical trial.…”
Section: Effect Of Leptin On the Upper Airwaymentioning
confidence: 99%
“…Leptin resistance has multiple mechanisms, but limited permeability of the BBB plays a key role [95][96][97][98]. Berger and colleagues [71] administered leptin intranasally in mice in an effort to bypass the BBB. Intranasal leptin increased ventilation during NREM and REM sleep and decreased the number of oxygen desaturation events in REM sleep (Table 1).…”
Section: Animal Models Of Neuromuscular Response: Airflow Outcomesmentioning
confidence: 99%